Endotoxemia is Related to Systemic Inflammation and Atherosclerosis in Peritoneal Dialysis Patients - Szeto, Cheuk-Chun (American Society of Nephrology, 2008)
Background and objectives: Systemic inflammatory state is a hallmark of peritoneal dialysis (PD) patients, but its etiology remains obscure. Because circulating microbial products are an important cause of systemic immune activation in other conditions such as HIV infection, it was hypothesized that endotoxemia is a cause of systemic inflammatory state and atherosclerosis in PD patients. Design, setting, participants, & measurements: Plasma lipopolysaccharide (LPS) levels in 30 consecutive new PD patients were measured. The result was compared with serum C-reactive protein (CRP) level, peritoneal transport status, history of pre-existing cardiovascular diseases, and carotid intima media thickness (IMT) by Doppler ultrasound. Results: Among the 30 PD patients, there were 17 men. The average age was 53.7 ± 15.1 yr. The average endotoxin concentration of PD patients was 0.44 ± 0.18 EU/ml, which was significantly higher than that of patients with chronic kidney disease secondary to Ig-A nephropathy (IgAN) (0.035 ± 0.009 EU/ml, P < 0.0001) and the controls (0.013 ± 0.007 EU/ml, P < 0.0001). In PD patients, plasma LPS concentration had a significant correlation with serum CRP (r = 0.415, P = 0.025) and serum albumin level (r = −0.394, P = 0.034). In contrast, plasma LPS level did not correlate with Charlson's Comorbidity Index, peritoneal transport characteristics, or nutritional indices. Patients with pre-existing cardiovascular disease (CVD) had higher plasma LPS level than those without CVD (0.53 ± 0.19 versus 0.36 ± 0.16 EU/ml, P = 0.016). Plasma LPS level correlated with carotid IMT (r = 0.438, P = 0.016). Conclusions: It was found that endotoxemia was probably common in PD patients, and the degree of circulating endotoxemia might be related to the severity of systemic inflammation and features of atherosclerosis. This result suggests that endotoxemia may have a contributory role to the systemic inflammatory state and accelerated atherosclerosis in PD patients.